Improvisation as The Enhancer of Corporate Entrepreneurship - Przemysław ZBIEROWSKI; Milena GOJNY-ZBIEROWSKA (Communications of International Proceedings, 2020)
The paper aims at investigating the influence of improvisation on corporate entrepreneurship, understood as entrepreneurial orientation. Intuitively improvisation is closely connected to EO, surprisingly, there is very little theoretical and empirical evidence on that relation. The paper aims at closing that gap by empirically investigating the role that improvisation plays in enhancing corporate entrepreneurship. There is some empirical evidence on role of improvising in individual entrepreneurship (Hmieleski & Corbett, 2003; Baker, Miner & Eesley, 2003; Best & Gooderham, 2015). We use Hmieleski and Corbett’s (2006) framework of improvisation as three-dimensional construct (creativity-bricolage, pressure-stress, action-persistence) and entrepreneurial orientation as three-dimensional (innovativeness, proactiveness, risk taking) construct to investigate the impact of improvisation on individual components of EO. The research has been carried out on a sample of 406 senior managers from medium and large organisations. Improvisation has proven to have a moderate impact on entrepreneurial orientation. Moreover, different dimensions of improvisation influence components of EO in different way: creativity and bricolage have positive impact on innovativeness and proactiveness and pressure-stress has impact on propensity to take risk. The study has implications for the theory of corporate entrepreneurship by highlighting possible antecedents of EO. Moreover, the results are significant for business practice as they provide useful ways of promoting corporate entrepreneurship.
Keywords: improvisation; corporate entrepreneurship; entrepreneurial orientation